Perilaku Disfungsional dalam Pengukuran Kinerja Perusahaan - Patdono Suwignjo (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
Performance measurement system is a critical component of a management system. Unfortunately, the success rate of performance measurement system implementation is relatively low. Even from the implementation categorized as success, only few of them are effective. Dysfunctional behavior is one of the factors that makes the implementaion of a performance measurement system is ineffective. This paper tries to elaborate the dysfunctional behavior of employees in performance measurement system implementation. Three examples of dysfunctional behavior cases are presented. Finally, the paper tries to propose some methods for reducing dysfunctional behavior. The three cases show that the alignment of incentive system to performance (performance related pay scheme) and the fear of unable to meet performance target have driven employees to behave dysfunctionally. The cases also show that gaming and biasing are two forms of dysfunctional behaviour practiced by employees. To reduce dysfunctional behavior the paper proposes three methods, namely: reducing the proportion of incentives tied up to performance, implementing the appropriate KPIs, and utilizing counter measures..